Placement, Wording, and Interviewers: Identifying Correlates of Consent to Link Survey and Administrative Data - Sakshaug, Joseph; Tutz, Valerie; Kreuter, Frauke (Survey Research Methods, 2013)
Record linkage is becoming more important as survey budgets are tightening while at the same time demands for more statistical information are rising. Not all respondents consent to linking their survey answers to administrative records, threatening inferences made from linked data sets. So far, several studies have identified respondent-level attributes that are correlated with the likelihood of providing consent (e.g., age, education), but these factors are outside the control of the survey designer. In the present study three factors that are under the control of the survey designer are evaluated to assess whether they impact respondents' likelihood of linkage consent: 1) the wording of the consent question; 2) the placement of the consent question and; 3) interviewer attributes (e.g., attitudes toward data sharing and consent, experience, expectations). Data from an experiment were used to assess the impact of the first two and data from an interviewer survey that was administered prior to the start of data collection are used to examine the third. The results show that in a telephone setting: 1) indicating time savings in the wording of the consent question had no effect on the consent rate; 2) placement of the consent question at the beginning of the questionnaire achieved a higher consent rate than at the end and; 3) interviewers' who themselves would be willing to consent to data linkage requests were more likely to obtain linkage consent from respondents.